IMPLEMENTASI PENGATURAN UNITED NATIONS FRAME WORK CONVENTION ON CLIMATE CHANGE 1992 - Jeane Neltje Saly (Universitas Nasional, 2010)
United Nations Framework Convention on Climate Change 1992 (UNFCCC) isthe grand rules of implementation of each country to handle an environmental change in connecting with global warming, especially difining a policy problem in a way that was particularly helpful to policy makers.